2016
DOI: 10.3791/53327
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Electroencephalography Measurements for Comparison of Task-Specific Neural Efficiencies: Spatial Intelligence Tasks

Abstract: Spatial intelligence is often linked to success in engineering education and engineering professions. The use of electroencephalography enables comparative calculation of individuals' neural efficiency as they perform successive tasks requiring spatial ability to derive solutions. Neural efficiency here is defined as having less beta activation, and therefore expending fewer neural resources, to perform a task in comparison to other groups or other tasks. For inter-task comparisons of tasks with similar durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Similarly, Villanueva and colleagues have explored EDA and emotions during engineering exams in a statics course (Villanueva, ; Villanueva, Call, & Goodridge, ; Vallanueva, Valladares, & Goodridge, ). Approximately 20 sophomore engineering students were asked to complete an emotions self‐report while being tested on problems based on cutting planes and spatial ability (Call, Goodridge, Villanueva, Wan, & Jordan, ; Ruesch et al, ; Villanueva et al, ; Villanueva, Call, & Goodridge, ) as they wore EDA sensors and encephalography (EEG) monitors in a laboratory setting. The preliminary findings suggested that the order of test problems may influence the activation of students' prefrontal cortex and EDA arousal (Call et al, ; Ruesch et al, ; Villanueva et al, ), a response which paralleled changes in negative emotions (e.g., pride; unpublished findings, Villanueva et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Villanueva and colleagues have explored EDA and emotions during engineering exams in a statics course (Villanueva, ; Villanueva, Call, & Goodridge, ; Vallanueva, Valladares, & Goodridge, ). Approximately 20 sophomore engineering students were asked to complete an emotions self‐report while being tested on problems based on cutting planes and spatial ability (Call, Goodridge, Villanueva, Wan, & Jordan, ; Ruesch et al, ; Villanueva et al, ; Villanueva, Call, & Goodridge, ) as they wore EDA sensors and encephalography (EEG) monitors in a laboratory setting. The preliminary findings suggested that the order of test problems may influence the activation of students' prefrontal cortex and EDA arousal (Call et al, ; Ruesch et al, ; Villanueva et al, ), a response which paralleled changes in negative emotions (e.g., pride; unpublished findings, Villanueva et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Approximately 20 sophomore engineering students were asked to complete an emotions self‐report while being tested on problems based on cutting planes and spatial ability (Call, Goodridge, Villanueva, Wan, & Jordan, ; Ruesch et al, ; Villanueva et al, ; Villanueva, Call, & Goodridge, ) as they wore EDA sensors and encephalography (EEG) monitors in a laboratory setting. The preliminary findings suggested that the order of test problems may influence the activation of students' prefrontal cortex and EDA arousal (Call et al, ; Ruesch et al, ; Villanueva et al, ), a response which paralleled changes in negative emotions (e.g., pride; unpublished findings, Villanueva et al, ). Similar to Harley et al’s () work, Villanueva and colleagues found limited variance recorded by the EDA sensor as well as the EEG monitor, confirming the need to conduct multi‐modal studies under less experimentally controlled scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Villanueva and colleagues have reported using self-reports with electrodermal activity sensors [19], [20] while Goodridge, Call, and colleagues have used electroencephalogram monitors [21], [22] to study performance in an engineering statics course. Each study has developed methods to identify how the type of exam problem could influence the activation of students' pre-frontal cortex and EDA arousal [19]- [22], which influence student performance and learning of different engineering problems.…”
Section: Academic Emotions In Authentic Engineering Educationmentioning
confidence: 99%
“…Following protocols established by Villanueva and colleagues [19], [20] and Goodridge, Call, and colleagues [21], [22], participants were asked to wear a sports band on their non-dominant wrist one hour before the study started and to not consume (e.g., caffeine) or wear (e.g., hair spray, hair gel, topical medications) any products that may have interfered with the readings. The sports band allowed for accumulation of baseline sweat formation in order for the sensor to collect skin conductance readings [19].…”
Section: Experimental Layoutmentioning
confidence: 99%
See 1 more Smart Citation